AI in Crowd Management and Safety in Stadium Management - Bandewar, Raghvendra; Khandelwal, Deepali (Indian Journal of Computer Science, 2025)
Artificial intelligence (AI) in stadium administration has revolutionized fan interaction, security, and crowd control. Stadiums have the capacity to accommodate large number of people, it has been observed that crowd safety and management are crucial to avoid accidents, traffic jams, and security risks. AI will improve automatic response, real-time monitoring, and predictive analysis, which will improve overall productivity and the experience of the audience. The purpose of the present research is to develop a safer and more interactive stadium environment by integrating more AI with the stadium's management functions. This study will also investigate how AI enhances fan connection and optimizes crowd flow and security measures in stadium environments. Using only secondary data from industry reports, case studies, and scholarly journals, this study explores AI-based solutions for crowd control and safety. Stadium administrators can effectively manage sizable crowds thanks to intelligent technology like facial recognition, Internet of Things sensors, and machine learning scripts that facilitate real-time decision-making. Additionally, chatbots, smartphone apps, and captivating AR/VR experiences are examples of AI-powered engagement technologies that tailor fan experiences and increase visitor happiness. The findings of the research suggest that AI is transforming stadium management by making crowd control smarter, security faster, and fan experiences more interactive, but challenges like cost, ethics, and system integration need careful handling for a truly seamless and inclusive future. This study will empower stadium managers and organizers with AI-driven tools to enhance security, streamline crowd flow, and create an engaging, seamless fan experience, making events safer, smarter, and more enjoyable for everyone.